Boy trouble - Webb, Sarah (2011)
Her sassy teenage aunt writes an advice column. But what if Amy needs boy tips of her own? A witty, genuine take on the ups and downs of friends, family, and first romance. (Age 11 and up) Thirteen-year-old Amy Green has a lot to juggle: handling her divorced parents, minding her messy baby siblings, and navigating the snobby popular cliques at school. So when her cool but crazy seventeen-year old aunt, Clover lands a job giving advice for the teen mag THE GOSS, Amy jumps at the chance to help out as her sidekick. Of course Clover, being Clover, doesn't just want to answer readers' letters, she wants to solve their problems . . . personally.
5-8.
HL570L
3.7
Electronic reproduction.
SORA electronic book.
Keywords: SORA electronic book; Advice columns -- Fiction; Dating (Social customs) -- Fiction; Aunts -- Fiction